2017
DOI: 10.1111/mpp.12594
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the diversity of effector genes in the banana pathogen, Fusarium oxysporum f. sp. cubense, reveals evidence of horizontal gene transfer

Abstract: It is hypothesized that the virulence of phytopathogenic fungi is mediated through the secretion of small effector proteins that interfere with the defence responses of the host plant. In Fusarium oxysporum, one family of effectors, the Secreted In Xylem (SIX) genes, has been identified. We sought to characterize the diversity and evolution of the SIX genes in the banana-infecting lineages of F. oxysporum f. sp. cubense (Foc). Whole-genome sequencing data were generated for the 23 genetic lineages of Foc, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
137
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 54 publications
13
137
2
2
Order By: Relevance
“…spp. lilii and cubense (Czislowski et al., ; van Dam et al., ) suggests that SIX7 may be separable, both physically and functionally, from SIX10 and SIX12 . Moreover, SIX10 and SIX12 are not arranged in divergent orientation, and so cannot be transcribed coordinately from a shared promoter, as is the case for SIX3 and SIX5.…”
Section: Discussionmentioning
confidence: 99%
“…spp. lilii and cubense (Czislowski et al., ; van Dam et al., ) suggests that SIX7 may be separable, both physically and functionally, from SIX10 and SIX12 . Moreover, SIX10 and SIX12 are not arranged in divergent orientation, and so cannot be transcribed coordinately from a shared promoter, as is the case for SIX3 and SIX5.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, host-preference in FOSC is often polyphyletic [44-56]. Several studies revealed putative horizontal transfer events of effector genes between FOSC strains that infect the same host [40,57-59], indicating that horizontal transfer may play an important role in host switches [39,40,56,60,61]. Of the four accessory chromosomes in Fol4287, chromosome 14 is undoubtedly a pathogenicity chromosome: all fourteen SIX (Secreted In Xylem) genes – known effector genes in tomato-infecting Fusarium oxysporum – are located on chromosome 14 [62] (and our unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…lycopersici , which has two sequence variants of SIX8 (Schmidt et al , ), and f. sp. cubense , which has four sequence variants of SIX8 and three variants of SIX9 (Fraser‐Smith et al , ; Czislowski et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (2010) then demonstrated the LS regions of Fol could be horizontally transferred to a nonpathogenic strain, transforming it into a pathogen. Multiple studies have since hypothesized that the SIX genes have been horizontally transferred between formae speciales of F. oxysporum (Fraser-Smith et al, 2014;Laurence et al, 2015;Taylor et al, 2016;van Dam et al, 2017;Czislowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%